Factors associated with noncontact injury in collegiate soccer: A 12-team prospective study of NCAA division I men`s and women`s soccer - Curtis, R. M.; Huggins, R. A.; Benjamin, C. L.; Sekiguchi, Y.; Lepley, L. K.; Huedo-Medina, T. B.; Casa, D. J. (The American Journal of Sports Medicine, 2021)
Background: Multiteam, multi-institution prospective studies of both women`s and men`s sports are essential for collectively investigating injury and primary to the generalization and individualization of injury prevention strategies.